RGEC, Sustainability Reporting, and Financial Performance: A Study in Listed Banks in IDX 2013-2017 - Gunarsih, Tri; ., Setiyono; Sayekti, Fran; Novak, Tamas (KnE Social Sciences, 2019)
This study aims to analyze Risk Profile, Good Corporate Governance, Earning, and Capital (RGEC), Sustainability Reporting (SR) and financial performance (ROE and TQ) of the listed banks in the IDX. This research implements correlation and regression analysis. Base on data samples of 12 banks in 2013-2017, the results of this study show that GCG and RGEC positively correlated to performance (ROE and TQ), but there is no correlation between SR and performance. The regression analysis shows that risk profile (LDR), GCG, and Earning / rentability (ROA) are statistically significant influence ROE but only NPL and GCG that influence TQ while SR is not significant, both to ROE and TQ. These findings support the arguments that the better the RGEC, the higher the financial performance. Subject to data limitation of SR, this study could not give empirical evidence that the better the SR, the higher the firm performance.